ANALISIS KARAKTERISTIK MANAJEMEN WAKTU BELAJAR PESERTA DIDIK KELAS XI IPS SMA NEGERI 11 PONTIANAK - Sari, Yulinda; Wicaksono, Luhur; Putri, Amallia (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
This study aims to describe the characteristics of student learning time management in class XI IPS SMA Negeri 11 Pontianak using a quantitative approach and the form of research is a survey. The data source was 115 students of class XI IPS at SMA Negeri 11 Pontianak with a data collection tool in the form of a questionnaire. The results showed that the characteristics of students' learning time management in class XI IPS were in the "good" category with results percentage 72%, which means that students of class XI IPS can maximize their study time management. Specifically, it includes: (1) dividing time well is in the "enough" category with a percentage of 60%, (2) Learning readiness is in the "good" category with a percentage of 76%, (3) concentration while studying is in the category "good" with a percentage of 80%. Based on this description, it can be concluded that the analysis of the characteristics of study time management of students in class XI IPS SMA Negeri 11 Pontianak is on average in the "good" category, which means that students in class XI IPS are able to manage their study time well. Suggestions for BK teachers need to provide services with a more optimal understanding to students about the importance of managing time well in improving study time management.